2020
DOI: 10.3390/su12166551
|View full text |Cite
|
Sign up to set email alerts
|

Recent Literature about Urban Sprawl: A Renewed Relevance of the Phenomenon from the Perspective of Environmental Sustainability

Abstract: The urban sprawl phenomenon has attracted the attention of social researchers since the mid-20th century. It seemed that all relevant aspects had been extensively studied and that it would be difficult to produce new studies with significant contributions. However, in the last decade, we have witnessed a revival of the literature on urban sprawl for three main reasons: (i) the existence of new methodologies to measure the phenomenon based on digital cartography and geo-referenced information, (ii) new hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 58 publications
(64 reference statements)
0
25
0
Order By: Relevance
“…This review has shown that there is a significant amount of literature analyzing the relationships between sprawl and climate change and that there is a renewed interest in the topic [8]. These research efforts address different aspects of those relationships by pointing to a variety of direct and indirect links, depending on the factors and combination of factors considered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This review has shown that there is a significant amount of literature analyzing the relationships between sprawl and climate change and that there is a renewed interest in the topic [8]. These research efforts address different aspects of those relationships by pointing to a variety of direct and indirect links, depending on the factors and combination of factors considered.…”
Section: Discussionmentioning
confidence: 99%
“…A two-pronged approach was adopted for identifying and analyzing the pertinent literature probing the linkages between urban sprawl and climate change. The first step centered on 7 literature reviews published between 1994 to 2015 (since expanded to include two reviews published in 2020 [7,8]) (see Table 1) on urban sprawl per se, or the environmental impacts of sprawl. The works and research themes covered in these 7 reviews laid a solid foundation for further search, by allowing, firstly, to review definitions, conceptualizations, and characterizations of sprawl, and secondly, to identify potent keywords and combinations of keywords that address the linkages between sprawl, or key aspects of it, and climate change.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Archaeological precedents provide scholars, planners, and urban experts with complete case studies of low-density cities as they have grown, flourished, and declined over 500-or even 1500-year time spans (Hall, Penny, and Hamilton 2019;Klassen, Weed, and Evans 2018). The life cycles considered by most urban-sustainability experts come nowhere near this time frame (Güneralp and others 2017;Rubiera-Morollón and Garrido-Yserte 2020). If we wish to seriously discuss the design of sustainable and resilient cities for future generations, such archaeological case studies provide valuable experiential references, or 'natural experiments', to use the terminology of Jared Diamond and James Robinson (2010), and dissolve the assumed correlation between industrialization, capital markets, and low-density urbanism.…”
mentioning
confidence: 99%